IVC Filters: Challenges and Future Directions. (20th November 2014) - Kiguchi, Misaki M.; Dillavou, Ellen D.
Abstract : Since their introduction in 1973, inferior vena cava filters have evolved concurrent with advancing technology, and, therefore, their use has expanded due to broader indications for insertion. This paper focuses on the challenges and future directions of this trend, including a closer look at complications, retrieval rates, and cost-effectiveness.